Until Tuesday [compact disc, unabridged] : a wounded warrior and the golden retriever who saved him - Montalván, Luis Carlos (Brilliance Audio ; Distributed by Recorded Books, 2012)
A highly decorated captain in the U.S. Army, Luis Montalván never backed down from a challenge during his two tours in Iraq. After returning home, however, the pressures of his physical wounds, traumatic brain injury and crippling PTSD took their toll. Haunted by the war and in constant pain, Luis drank, argued, and cut himself off from those he loved. Then he met Tuesday, a beautiful and sensitive service dog who had trouble trusting humans--until Luis.